Predictability of Polish Zloty exchange rates against EURO on the basis of levels of macroeconomic fundamentals and national stock market behaviour - Malinowska, Martyna (2011)
Investors have been looking for ways of predicting Foreign Exchange Market movements in order to hedge their positions in international trade or cash in a profit. The study focuses on the investigation of factors which can serve as a mean of predicting exchange rates of Polish currency against EURO in short and long time horizon between 1997-2011. After reviewing available literature, macroeconomic fundamentals such as inflation rate, interest rate and terms of trade have been selected for the analysis in the long time horizon. Daily capitalization of Polish national equity index- WIG, is implemented in the study of short time horizon. Predictive power of macroeconomic fundamentals and stock market was tested under different economic environment such as stage of capital market development, different exchange rate regime as well as strict and liberal monetary and fiscal policy of Polish National Bank and policymakers.